Kriteria Penahapan Perkembangan : Kriteria Penahapan Perkembangan - Maryam Paso; Evandri Paputungan; Zihan Usman; Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2021)
A criterion is a measure that forms the basis for evaluating or determining something. Stages in KBBI are: process, method, act of staging. The process of human development has 8 stages from infancy to old age. The developmental stage criterion is a system for evaluating a child's progress in terms of physical, emotional, cognitive, and social abilities. The purpose of this criterion is to ensure that children experience reasonable development and according to their age. The criteria for the stages of development are based on the stages that have been determined in several areas of child development. These stages can be used to help identify children who may need special developmental assistance. In this article, we will discuss the criteria for the stages of development and developmental stages in children.